2015
DOI: 10.1212/wnl.0000000000001877
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-β 11 C-PiB-PET imaging results from 2 randomized bapineuzumab phase 3 AD trials

Abstract: Objective: To evaluate the effects of bapineuzumab on brain b-amyloid (Ab) burden using 11 C-Pittsburgh compound B ( 11 C-PiB)-PET.Methods: Two phase 3 clinical trials, 1 each in apolipoprotein APOE e4 carriers and noncarriers,were conducted in patients with mild to moderate Alzheimer disease dementia. Bapineuzumab, an anti-Ab monoclonal antibody, or placebo, was administered by IV infusion every 13 weeks for 78 weeks. PET substudies assessed change in brain fibrillar Ab over 71 weeks using an 11 C-PiB-PET sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
95
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(101 citation statements)
references
References 25 publications
3
95
0
2
Order By: Relevance
“…Although the lack of cognitive improvement in the Gammagard trials is discouraging, there is a growing consensus that AD will likely have to be tackled during the prodromal phase with primary or secondary prevention trials, as even Aβ-targeting antibodies have failed to improve cognition in phase III trials (44,45). It is therefore quite possible that Gammagard or other IgG formulations, perhaps combined with transient permeabilization of the BBB through focused ultrasound, might provide increased benefit if tested in prodromal AD.…”
Section: Discussionmentioning
confidence: 99%
“…Although the lack of cognitive improvement in the Gammagard trials is discouraging, there is a growing consensus that AD will likely have to be tackled during the prodromal phase with primary or secondary prevention trials, as even Aβ-targeting antibodies have failed to improve cognition in phase III trials (44,45). It is therefore quite possible that Gammagard or other IgG formulations, perhaps combined with transient permeabilization of the BBB through focused ultrasound, might provide increased benefit if tested in prodromal AD.…”
Section: Discussionmentioning
confidence: 99%
“…Among many other applications, amyloid-b imaging has been incorporated into diagnostic criteria for various stages of the disease (Albert et al, 2011;McKhann et al, 2011;Sperling et al, 2011;Dubois et al, 2014), has substantial impact on clinical decision-making (Ossenkoppele et al, 2013a;Sanchez-Juan et al, 2014) and patient management plans (Schipke et al, 2012;Grundman et al, 2013), and has shown potential as a surrogate outcome measure in clinical trials tailored to reduce cerebral amyloid-b plaque burden (Salloway et al, 2014;Liu et al, 2015). A yet unresolved issue after a decade of amyloid-b imaging research, however, is the disconnection between the diffuse distribution of amyloid-b pathology throughout the neocortex (Rabinovici et al, 2010;Wolk et al, 2012;Lehmann et al, 2013;Jung et al, 2015) and the selective patterns of brain atrophy and glucose hypometabolism that strongly correlate with clinical symptoms (Rabinovici et al, 2010;Ridgway et al, 2012;Lehmann et al, 2013;Madhavan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Two additional trials with the same structure of ApoE 4 carriers and noncarriers were conducted in multiple countries with a similar lack of functional effectiveness, but without adverse effects [26]. Other studies have reported improved brain volume in imaging and plaque reduction in patients treated with bapineuzumab [27,28], but the relevance of these observations is not clear since functional studies have reported no significant benefits.…”
Section: First-generation Anti-aβ42 Antibodiesmentioning
confidence: 99%